Single-cell transcriptomic analysis of oligodendrocyte lineage cells - van Bruggen, David; Agirre, Eneritz; Castelo-Branco, Gonçalo (Current opinion in neurobiology, 2017)
•Several studies catalogued central nervous system cell types by bulk and single-cell RNA-seq.•An unexpected heterogeneity of oligodendrocyte lineage cells is starting to emerge.•Does a given cell cluster ultimately constitute a cell type or cell state?•Functional studies will be required to address whether a transcriptional state is constitutive or transient, and thus a cell type or state. Oligodendrocytes (OLs) are glial cells in the central nervous system (CNS), which produce myelin, a lipid-rich membrane that insulates neuronal axons. The main function ascribed to OLs is to regulate the speed of electric pulse transmission, and as such OLs have been widely considered as a single and discrete population. Nevertheless, OLs and their precursor cells (OPCs) throughout the CNS have different morphologies and regional functional differences have been observed. Moreover, OLs have recently been involved in other functional processes such as metabolic coupling with axons. In this review, we focus on recent advances in single-cell transcriptomics suggesting that OLs are more heterogeneous than previously thought, with defined subpopulations and cell states that are associated with different stages of lineage progression and might also represent distinct functional states.